From Sacred Ritual to Cultural Festival: The Transformation of the Dreadlocked Hair Ruwatan Tradition in Dieng as a Cultural Practice - Fitri Rosanti,; M. Fadhilah,; Muhammad Ijlal Sasakki Junaidi, (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The Hair Dreadlocks Ruwatan Ritual in the Dieng Plateau, particularly in Dieng Kulon Village, is a sacred tradition of Javanese society that represents a complex relationship between spirituality, local cosmology, ritual arts, and social structure. Dreadlocked hair is not understood merely as a biological phenomenon, but as a symbol of an individual’s connection with ancestors and supernatural forces, thus requiring a ruwatan ritual to restore physical, emotional, and spiritual balance. This study aims to examine the spiritual and philosophical meanings of dreadlocked hair, the structure and stages of the ruwatan ritual, the role of art and cultural expression, and the dynamics of social transformation in the context of modernization and cultural tourism. This research employs a descriptive qualitative approach using a case study method. Data were collected through participant observation, in-depth interviews with traditional leaders and cultural practitioners, and documentation, and were analyzed using thematic analysis. The findings indicate that the dreadlocks ruwatan ritual has multidimensional meanings as a purification rite, a medium of cosmological communication, and a mechanism for strengthening the cultural identity of the Dieng community. The ritual structure is carried out systematically based on genealogical legitimacy and the spiritual authority of customary leaders, while artistic elements such as gamelan music, Javanese chanting (kidungan), traditional attire, and ritual spatial arrangements reinforce the sacred atmosphere and collective spiritual experience. At the same time, the ritual has undergone a transformation from a private family practice into a public festival that functions both as a sacred rite and a cultural attraction, giving rise to negotiations between sacred values, cultural economy, religious discourse, and digital media representation. This study concludes that the dreadlocks ruwatan ritual is a living and adaptive tradition that is able to maintain its spiritual core while responding to contemporary social dynamics without losing its cultural and religious significance.